The Activity of the Chloroplastic Ndh Complex Is Regulated by Phosphorylation of the NDH-F Subunit - Lascano, Hernan Ramiro; Casano, Leonardo M.; Martı́n, Mercedes; Sabater, Bartolomé (American Society of Plant Biologists, 2021)
Hydrogen peroxide (H2O2) induces increases, to different degrees, in transcripts, protein levels, and activity of the Ndh complex (EC 1.6.5.3). In the present work, we have compared the effects of relatively excess light, H2O2, dimethylthiourea (a scavenger of H2O2), and/or EGTA (a Ca2+chelator) on the activity and protein levels of the Ndh complex of barley (Hordeum vulgare cv Hassan) leaf segments. The results show the involvement of H2O2 in the modulation of both the protein level and activity of the Ndh complex and the participation of Ca2+ mainly in the activity regulation of pre-existing protein. Changes in Ndh complex activity could not be explained only by changes in Ndh protein levels, suggesting posttranslational modifications. Hence, we investigate the possible phosphorylation of the Ndh complex both in thylakoids and in the immunopurified Ndh complex using monoclonal phosphoamino acid antibodies. We demonstrate that the Ndh complex is phosphorylated in vivo at threonine residue(s) of the NDH-F polypeptide and that the level of phosphorylation is closely correlated with the Ndh complex activity. The emerging picture is that full activity of the Ndh complex is reached by phosphorylation of its NDH-F subunit in a H2O2- and Ca2+-mediated action.